Approximation of Fixed Points In CAT(0) Spaces Using A New Three-Step Iteration Process For Asymptotically Quasi-Nonexpansive Mapping - Verma, Anurag; Tripathi, B.P. (International Journal of Membrane Science and Technology, 2023)
In this paper, we introduce a new three-step iteration scheme and establish convergence results for the approximation of fixed points of asymptotically quasi-nonexpansive mapping in the framework of CAT(0) space and also give an example of a nonlinear function that is asymptotically quasi-nonexpansive but it is not quasi-nonexpansive. Finally, we display the efficiency of the proposed scheme compared to different iterative schemes by a numerical example in the literature. Our results generalize and improve many well-known results in the literature of iterations in fixed point theory.